Kazakh national culture and ceremonies as a philosophy of ethnic identity - Kulbekova, Aigul; Tleubayev, Seraly; Bakirova, Gulmira; Kabdusova, Dina; Tleubayeva, Balzhan; Mambetova, Gulnara (Opción, 2019)
The purpose of our research is to identify new areas and trends in the development of Kazakh dance through the example of the creative activity of the Kazakh leading choreographic groups. The historical and theoretical analysis of the problem showed that the formation of the Kazakh dance culture was affected by the activities, life, folklore, talent, and imagination of many generations. In conclusion, the dance forms of folk choreography were improved with the course of time and acquired artistic value and completeness with each era.